Worry and Positive Episodes in the Daily Lives of Individuals With Generalized Anxiety Disorder: An Ecological Momentary Assessment Study - Vîslă, Andreea; Zinbarg, Richard; Hilpert, Peter; Allemand, Mathias; Flückiger, Christoph (Frontiers in Psychology, 2021)
Worry is a central feature of generalized anxiety disorder (GAD). Although worry is related to anxiety and maintained by beliefs that worry is uncontrollable, there is scarce research on how individuals with GAD react to worry episodes in their daily life and how their positive experiences might impact reactions to worry episodes. The current study examined the level and variability of anxiety and controllability during high worry periods and positive experiences in GAD. Moreover, it investigated the influence of worry and positive experiences on later anxiety and perceived controllability within-persons. Finally, it examined change in anxiety level from previous to current episodes depending on previous episodes type. In the current study, 49 individuals with GAD (514 observations) registered their worry and positive episodes (i.e., episodes in which they had positive experiences) and reported on several variables during these episodes (i.e., anxiety and controllability of episodes and episode duration) using smartphone-based ecological momentary assessment for 7days. Results show anxiety and controllability differed by episode type (higher anxiety, lower controllability in worry episodes, and the opposite in positive episodes), and notable within-person variability in anxiety and controllability in both episode types. The time-lagged multilevel models showed episode type did not predict later anxiety during either episode type, although previous anxiety predicted current anxiety in worry episodes (but not positive episodes). Moreover, worry episodes did predict later controllability in worry episodes (but not positive episodes) and previous controllability predicted current controllability in both episode types. Furthermore, we obtained the increase in anxiety from t0−1 to t0 in a current worry episode to be significantly smaller when preceded by a worry (vs. positive) episode. Likewise, the reduction in anxiety from t0−1 to t0 in a current positive episode was significantly larger when preceded by a worry (vs. positive) episode. The novel findings in the current study that perceptions of controllability and anxiety vary within individuals with GAD, that greater controllability is experienced in positive episodes than worry episodes, and that worry may confer a sense of controllability at a later time could be seen as important contributions to the GAD literature.